PENGARUH LIKUIDITAS, PENDAPATAN NON-BUNGA, PROFITABILITAS DAN LEVERAGE TERHADAP KECUKUPAN MODAL : Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2018–2021 - Thomas Sumarsan Goh; Arthur Simanjuntak; Edison Sagala (Jurnal Ilmu Manajemen METHONOMIX, 2023)
This study is to examine the effect of liquidity, non-interest income, profitability, and leverage on Capital Adequacy Ratio. The sampling technique used is Purposive sampling. The data collection technique is the study of documentation. Data analysis using análisis multiple linear regression. Investing Policy Ratio, Non Interest Income, Loan Asset Ratio and Financing to Deposit Ratio has no effect on the Capital Adequacy Ratio, Deposit Asset Ratio has a negative and significant effect on Capital Adequacy Ratio, Net Profit Margin has a positive and significant effect on Capital Adequacy Ratio in banking companies listed on the Indonesia Stock Exchange for the period 2018-2021. Investing Policy Ratio, Loan to Asset Ratio, Financing to Deposit Ratio, Non Interest Income, Net Profit Margin, and Deposit Asset Ratio have a positive and significant effect on the Capital Adequacy Ratio in banking companies listed on the Indonesia Stock Exchange for the period 2018-2021.